2021
DOI: 10.2147/copd.s340113
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the Nrf2 Promoter Induces Ferroptosis by Inhibiting the Nrf2-GPX4 Axis in COPD

Abstract: Background Nuclear factor E2-related factor 2 (Nrf2) is involved in oxidative stress and lung inflammation and regulates the etiology of chronic obstructive pulmonary disease (COPD). Ferroptosis is characterized by the accumulation of lipid reactive oxygen species (ROS) via ferrous ion-dependent Fenton reactions and is involved in COPD. However, the role of Nrf2 in ferroptosis and its epigenetic regulation in the pathogenesis of COPD remain unclear. Methods Ferroptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Mice in the CSE+LV-shNC and CSE+LV-shACSL4 groups received intratracheal infusions of Lentiviral vector containing unrelated sequence (LV-shNC) (Fenghbio, BR004, Changsha, Hunan, China) and Lentiviral vector containing ACSL4 (LV-shACSL4) (10 8 TU/mL) (Fenghbio, BR004, Changsha, Hunan, China) on Day 14, respectively, while mice in the control and CSE groups received intratracheal transfusions of an equal volume of PBS on Day 14. 12 , 13 Each group of mice was sacrificed on Day 28, and lung tissue was collected for follow-up assessments. Before being sacrificed on Day 28, the respiratory frequency (f) and the enhanced pause (Penh) of the mice in each group were detected with a non-invasive pulmonary function testing system for small animals (analog interface-16, Emka, France).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice in the CSE+LV-shNC and CSE+LV-shACSL4 groups received intratracheal infusions of Lentiviral vector containing unrelated sequence (LV-shNC) (Fenghbio, BR004, Changsha, Hunan, China) and Lentiviral vector containing ACSL4 (LV-shACSL4) (10 8 TU/mL) (Fenghbio, BR004, Changsha, Hunan, China) on Day 14, respectively, while mice in the control and CSE groups received intratracheal transfusions of an equal volume of PBS on Day 14. 12 , 13 Each group of mice was sacrificed on Day 28, and lung tissue was collected for follow-up assessments. Before being sacrificed on Day 28, the respiratory frequency (f) and the enhanced pause (Penh) of the mice in each group were detected with a non-invasive pulmonary function testing system for small animals (analog interface-16, Emka, France).…”
Section: Methodsmentioning
confidence: 99%
“…The mean linear intercept (MLI) and destructiveness index (DI) were measured to assess emphysema. 12,13 https://doi.org/10.2147/COPD.S391129…”
Section: Haematoxylin-eosin (Hande) Stainingmentioning
confidence: 99%
“…Recent studies reported that CpG hypermethylation in the promoter causes downregulation of Nrf2 expression in the lung tissue of patients with COPD (65). Zhang et al found that, in HBE cells treated with CSE, the expression levels of reactive oxygen species (ROS), lipid peroxides, and MDA are increased, and they also reported that the levels of IL-1β and IL-8 are increased but that the expression levels of GPX4 and SOD are decreased, indicating that CSE induces ferroptosis in HBE cells and increases the release of inflammatory factors (63). However, increasing the expression of Nrf2 enhances the expression of GPX4 and SOD but inhibits the expression of ferroptosis and related inflammatory factors in the supernatant.…”
Section: Role Of Ferroptosis In Copdmentioning
confidence: 99%
“…Hypermethylation of the nuclear factor erythroid 2-related factor 2 (Nrf2) promoter could inhibit Nrf2/GPX4 axis, thus affecting ferroptosis in COPD. 10 Otherwise, many studies suggest that various immune cells play vital roles in chronic airway diseases such as COPD. Innate immune cells, which were enhanced in small airways, modulated airway inflammation and remodeling.…”
Section: Introductionmentioning
confidence: 99%